INCOME TAX (PPH) 21 CALCULATION APPLICATION - Panjaitan, Muhammad Adriansyah Safii; sanjaya, surya; irsan, Muhammad (CERED Indonesia Institute, 2024)
The year 2024 begins with the implementation of the use of the average effective rate, or often referred to as TER. The TER scheme is used to calculate the amount of Article 21 Income Tax (PPh 21), the TER policy is regulated in Government Regulation Number 58 of 2023. The calculation of Article 21 Income Tax uses two calculation schemes, namely the monthly PPh Article 21 calculation scheme using the TER rate scheme, while the calculation of Article 21 Income Tax in the end-of-year tax period or December uses the rate of Article 17 paragraph (1) of the Income Tax Law. The calculation of Article 21 Income Tax deductions using the TER rate deducted from the gross income of permanent employees uses the monthly rates of categories A, B, and C which are adjusted to the marital status of the taxpayer and each rate category consists of 30 layers of rates.